Cryopreservation in ART and concerns with contamination during cryobanking. (5th February 2014) - Larman, Mark G.; Hashimoto, Shu; Morimoto, Yoshiharu; Gardner, David K.
Abstract: The cryopreservation of gametes and embryos is vital to numerous fields of reproductive biology, including assisted human reproduction. With improved culture conditions, there are an increasing number of embryos to cryopreserve for potential use in subsequent cycles. Many of the gametes and embryos in human IVF are cryopreserved in open systems. Because liquid nitrogen is not sterile, concerns have been raised with regard to contamination from the liquid nitrogen and also cross‐contamination between patients' germplasm. Human gamete and embryo cryopreservation are discussed, with recommendations on how to minimize and eliminate contamination, emphasizing the benefits of closed vitrification devices.